Searching for magnetostatic modes in spin-polarized atomic hydrogen - L Lehtonen; O Vainio; J Ahokas; J Järvinen; S Sheludyakov; K-A Suominen; S Vasiliev (IOP PUBLISHING LTD, 2025)
We consider a possibility of the magnetostatic type spin waves driven by a long-range magnetic dipole interactions, to account for the peaks in the ESR spectra observed in our previous work (Lehtonen et al 2018 New J. Phys. 20 055010). The Walker equation for magnetostatic modes is solved for a cylinder of atomic hydrogen, first in a uniform magnetic field and second in a linearly decreasing magnetic field. The frequency behavior of the solved modes with length of the cylinder and density of the gas is compared to experimental data. We conclude that magnetostatic modes are unlikely to account for the observed modulations of ESR spectra.